Immersive Positive Psychological Interventions: a qualitative measuring in a controlled VR trial - Kunst, Marina Holanda; Silva, Eliane De Holanda; Peres, Fabiana; Nunes, Fatima; Teixeira, João Marcelo (Anais do Simpósio de Realidade Virtual e Aumentada (SVR), 2025)
Immersive virtual reality (VR) platforms have matured to the point where they can host evidence-based psychological interventions with high ecological validity and low logistical cost, yet few studies have examined their feasibility within routine clinical practice in Brazil. We introduce [OMMITTED DUE TO BLIND REVIEW], a suite of eight purpose-built environments grounded in the DAHLIA protocol, and report the first controlled pilot trial of the system in an outpatient setting. Thirty adults completed up to three therapist-guided VR sessions on a Meta Quest 3; eighteen of them experienced the flagship Japanese-Garden scene analyzed here. Pre-/post mood ratings, session-by-session qualitative feedback and adverse-event logs were collected. Across all exposures no moderate or severe cybersickness was recorded. Immediate affective change was uniformly neutral-to-positive, with 72% of sessions producing a shift of at least one valence category (e.g. "anxious" → "calm"). Qualitative comments became progressively more elaborate and immersive across sessions, suggesting a familiarity-driven gain in presence and engagement. The findings demonstrate that strengths-oriented VR can be delivered safely, acceptably and with preliminary mood benefits in Brazilian clinical practice. They lay the groundwork for larger randomized trials to establish long-term efficacy and optimal dosing schedules.